The Influence of Further Study Information Services on The Interest of Enterprising Students of SMK Negeri 2 Mataram - Mohammad Archi Maulyda; Siti Istiningsih; Sukardi Sukardi; Uwi Martayadi; Anton Budiharjo (Universitas Negeri Padang, 2021)
This study aims to determine whether the guidance of further study information services affects the higher education interest of students of SMKN 2 Mataram. This study uses a quantitative research approach with the Pre-Experimental Design method in the form of One-Group Pretest-Posttest Design. The variables of this research are the interest in entering higher education and the independent variable of further study information service guidance. The study population was SMKN 2 Mataram, while the sample was students of class XI who attended further study information service guidance, namely 36 (thirty) students, who were determined by incidental sampling technique. Based on the results of data analysis with SPSS 17.0 for windows software with the Paired Sampe t Test procedure, the results show that t is greater than t table, t (count) (3.986)> t (table) (1.690). So the hypothesis of this research: there is an effect of further study information services on student interest in learning at SMKN 2 Mataram is accepted. The results of this study prove that information services for further studies have an effect on student interest in entering higher education. Therefore, it can be used as input and material for consideration for Guidance and Counseling Teachers in order to increase their role in directing vocational students who intend to continue to a higher level of education after completing their studies.